Genetic and morphological variation and differentiation of Raja clavata populations in the European seas: marker development and preliminary data - Castaman, Giovanni (Alma Mater Studiorum - Università di Bologna, 2014)
In this study the population structure and connectivity of the Mediterranean and Atlantic Raja clavata (L., 1758) were investigated by analyzing the genetic variation of six population samples (N = 144) at seven nuclear microsatellite loci. The genetic dataset was generated by selecting population samples available in the tissue databases of the GenoDREAM laboratory (University of Bologna) and of the Department of Life Sciences and Environment (University of Cagliari), all collected during past scientific surveys (MEDITS, GRUND) from different geographical locations in the Mediterranean basin and North-east Atlantic sea, as North Sea, Sardinian coasts, Tuscany coasts and Cyprus Island. This thesis deals with to estimate the genetic diversity and differentiation among 6 geographical samples, in particular, to assess the presence of any barrier (geographic, hydrogeological or biological) to gene flow evaluating both the genetic diversity (nucleotide diversity, observed and expected heterozygosity, Hardy- Weinberg equilibrium analysis) and population differentiation (Fst estimates, population structure analysis). In addition to molecular analysis, quantitative representation and statistical analysis of morphological individuals shape are performed using geometric morphometrics methods and statistical tests. Geometric coordinates call landmarks are fixed in 158 individuals belonging to two population samples of Raja clavata and in population samples of closely related species, Raja straeleni (cryptic sibling) and Raja asterias, to assess significant morphological differences at multiple taxonomic levels. The results obtained from the analysis of the microsatellite dataset suggested a geographic and genetic separation between populations from Central-Western and Eastern Mediterranean basins. Furthermore, the analysis also showed that there was no separation between geographic samples from North Atlantic Ocean and central-Western Mediterranean, grouping them to a panmictic population. The Landmark-based geometric ...